Animated Video Learning Media for the IPAS Subject on Plant Body Parts for Fourth Grade Elementary School Students - Imamah, Fauzatul; Suartama, I Kadek; Sukmana, Adrianus I Wayan Ilia Yuda (Jurnal Media dan Teknologi Pendidikan, 2025)
Learning of IPAS (Science, Environment, and Social Studies) in elementary schools is often hindered by the lack interactive media that can simplify abstract concepts such as the parts of plant bodies. This leads to low motivation and understanding among students. This study aims to design, evaluate the validity, and measure the effectiveness of animated video learning media to optimize learning outcomes for fourth-grade elementary students. Using ADDIE model (Analysis, Design, Development, Implementation, Evaluation), involved 3 experts (content, design, and media), 3 students in individual trials, and 6 students in small group trials. Data was collected through questionnaires and tests, then analyzed using descriptive quantitative techniques and t-tests. The results showed excellent validity: 96% (content expert), 85.45% (design expert), 92.63% (media expert), 95.14% (individual trial), and 93.63% (small group trial). The media's effectiveness was proven by an increase in scores from 28.83 (pretest) to 85.33 (posttest) (tcount = 38.157 > ttable = 2.045). This media is effective in improving IPAS learning outcomes. The implication is that media can be integrated into the Independent Curriculum to support interactive and technology-based learning.